2022
DOI: 10.1186/s12889-022-13467-4
|View full text |Cite|
|
Sign up to set email alerts
|

Community-based care models for arterial hypertension management in non-pregnant adults in sub-Saharan Africa: a literature scoping review and framework for designing chronic services

Abstract: Background Arterial hypertension (aHT) is the leading cardiovascular disease (CVD) risk factor in sub-Saharan Africa; it remains, however, underdiagnosed, and undertreated. Community-based care services could potentially expand access to aHT diagnosis and treatment in underserved communities. In this scoping review, we catalogued, described, and appraised community-based care models for aHT in sub-Saharan Africa, considering their acceptability, engagement in care and clinical outcomes. Additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…(61). According to a recent scoping review, our two TwiCs will be the rst to assess a multifaceted, communitybased, VHW-led aHT care intervention including pharmacological treatment in Africa (24).…”
Section: Discussionmentioning
confidence: 99%
“…(61). According to a recent scoping review, our two TwiCs will be the rst to assess a multifaceted, communitybased, VHW-led aHT care intervention including pharmacological treatment in Africa (24).…”
Section: Discussionmentioning
confidence: 99%
“…These programs have grown in part from models built for the treatment of HIV and tuberculosis. 64 All offered different elements of task shifting or The market landscape for hypertension remote monitoring companies and programs is large and complex, comprising an array of comprehensive programs, services, products, and devices. Provided by: Manatt Health, November 3, 2022.…”
Section: Accessibility and Health Equitymentioning
confidence: 99%
“…These programs have grown in part from models built for the treatment of HIV and tuberculosis. 64 All offered different elements of task shifting or task sharing, but doctors played a substantial role in the majority. Although most reported significant reductions in BP, studies were marked by high attrition rates and high risk of bias; work is urgently needed to assess optimal future care models in these settings.…”
Section: Key Challengesmentioning
confidence: 99%
“…Another systematic review and meta-analysis on the effect of community-based programs on diabetes prevention in low- and middle-income countries 1 revealed that such programs had positive outcomes on patients at risk of T2DM. A recent scoping review indicates substantial potential of community-based care models for arterial hypertension in SSA 21 . Moving care of uncomplicated cases and low-risk groups to the community level and to non-physician health workers who are themselves supervised by higher health cadres, has advantages including fewer clinic visits, not having to travel long distances, not waiting in queues, and freeing up medical services in the facility for complicated cases and high-risk groups.…”
Section: Introductionmentioning
confidence: 99%